2008
DOI: 10.1002/bmc.1134
|View full text |Cite
|
Sign up to set email alerts
|

Microseparation techniques for the study of the enantioselectivity of drug–plasma protein binding

Abstract: Stereoselectivity in protein binding can have a significant effect on the pharmacokinetic and pharmacodynamic properties of chiral drugs. The investigation of enantioselectivity of drugs in their binding with human plasma proteins and the identification of the molecular mechanisms involved in the stereodiscrimination by the proteins represent a great challenge for clinical pharmacology. In this review, the separation techniques used for enantioselective protein binding experiments are described and compared. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…As stated in the introduction, the methodology was already proposed, optimised and validated by the authors ( [4,6,7] and references therein), and the data found in this case exhibit the same pattern found in previously reported results for other drugs. Therefore, only the specific information concerning to PRO is reported here.…”
Section: Evaluation Of Enantioselective Binding Of (±)-Pro Enantiomersupporting
confidence: 80%
See 1 more Smart Citation
“…As stated in the introduction, the methodology was already proposed, optimised and validated by the authors ( [4,6,7] and references therein), and the data found in this case exhibit the same pattern found in previously reported results for other drugs. Therefore, only the specific information concerning to PRO is reported here.…”
Section: Evaluation Of Enantioselective Binding Of (±)-Pro Enantiomersupporting
confidence: 80%
“…A review of our group [4] emphasised the microseparation techniques for evaluating the enantioselective binding of drugs to plasma proteins. It includes several reports using a methodology that allowed us to perform the study from the racemate of the target molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Some methods have been proposed to assess protein-binding capabilities based on diverse analytical tools 16,24,25 . Gilabert et al 26 established 3 steps to study the stereoselective binding between enantiomers and proteins: 1) equilibration of racemic mixture and proteins, 2) separation of the unbound fraction, and 3) determination of the concentration of the enantiomers from either the free fraction or drug-protein complexes.…”
Section: Methods and Modelsmentioning
confidence: 99%
“…In fact, very often one of them is most active while the other may produce side‐effects and even toxicity in some cases (Asensi‐Bernardi et al , ). Therefore, investigation of the enantioselectivity of drugs in their pharmacokinetic and pharmacological properties represents a great challenge for clinical pharmacology (Escuder Gilabert et al , ). Under pressure from authorities, there has been an increasing interest in development of rapid, efficient and sensitive analytical methods to control the chiral purity of drugs and for pharmacokinetic studies (Cherkaoui et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…The most important bioanalytical approaches to characterizing drug–protein binding have been recently reviewed, including a critical evaluation of their strengths and weaknesses (Vuignier et al , ). A review of our group emphasized the microseparation techniques for evaluating the enantioselective binding of drugs to plasma proteins (Escuder Gilabert et al , ). Most in vitro studies concerning a racemate involve two steps: separation of the free drug fraction from the bound drug once the drug–protein equilibrium has been reached, and chiral analysis of enantiomers, usually on the unbound fraction.…”
Section: Introductionmentioning
confidence: 99%